Variable doping sensitivity of the TO phonon dispersion branch of metallic nanotubes: A double resonant Raman scattering study - Rafailov, Peter M.; Maultzsch, Janina; Thomsen, Christian; Dettlaff-Weglikowska, Urszula; Roth, Siegmar (physica status solidi (b), 2009)
We applied Raman spectroscopy to investigate the response to electrochemical doping of the second-order D*-band in single-walled carbon nanotube (SWNT) bundles. A dramatic increase of the D*-band sensitivity to doping is found upon moving the laser excitation to the red end of the visible spectrum and beyond. Basing on the double resonance (DR) Raman scattering model we interpret this phenomenon as an increasing doping sensitivity of the TO phonon dispersion branch of metallic SWNTs towards its minimum. From D*-band measurements we are thus able to draw conclusions on the wave-vector dependence of the doping sensitivity and the electron-phonon coupling (EPC) around the TO branch minimum. (C) 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim